THE IMPACT OF FACILITIES AND EQUIPMENT ON THE ACHIEVEMENT OF COACHES IN NIGERIAN UNIVERSITIES (FUDMA JOURNAL OF SCIENCES, 2023)
This study was to find out the impact of facilities and equipment on the achievement of Coaches in Nigerian Universities. The population of this study consists of coaches, administrators and athletes from the first generation universities. A questionnaire was prepared which were validated by four experts from the Departments of Public Administration and Physical and Health Education of Ahmadu Bello University, Zaria. The sample was drawn from the 52 members of Nigerian Universities Games Association (NUGA). The statistical techniques used for this study was; frequency  and percentages to determine the demographic characteristics of respondents while multiple correlation was used to determine the interrelationship between the variables, and Pearson Product Moment Correlation was used to correlate the various variables for the study. The findings of the study revealed; that there was no significant relationship between  facilities and equipment on the achievement of coaches in Nigerian Universities The study recommended that University management should set aside one evening as free lecture day to enable students have opportunity to train and recreate as declared by National Universities Commission, Adequate facilities and equipment should be provided to enhance the performance of coaches and athletes in Nigerian Universities
Keywords: Achievement, administrative support, coaches, equipment, facilities, impact.